Predictors for Stroke and Death in Non-Anticoagulated Asian Patients with Atrial Fibrillation: The Fushimi AF Registry. - Yasuhiro Hamatani; Yugo Yamashita; Masahiro Esato; Yeong-Hwa Chun; Hikari Tsuji; Hiromichi Wada; Koji Hasegawa; Mitsuru Abe; Gregory Y H Lip; Masaharu Akao (PLoS ONE, 2015)
Atrial fibrillation (AF) increases the risk of stroke and death. Data on the predictors for stroke and death in 'real-world' AF patients are limited, especially from large prospective Asian cohorts.The Fushimi AF Registry is a community-based prospective survey designed to enroll all AF patients who visited the participating medical institutions in Fushimi-ku, Kyoto, Japan. Follow-up data were available for 3,304 patients (median follow-up period 741 days). We explored the predictors for 'death, stroke, and systemic embolism (SE)' during follow-up in 1,541 patients not receiving oral anticoagulants (OAC) at baseline.The mean age was 73.1 ± 12.5 years, and 673 (44%) patients were female. The mean CHADS2 and CHA2DS2-VASc scores were 1.76 and 3.08, respectively. Cumulative events were as follows: stroke/SE in 61 (4%) and death in 230 (15%), respectively. On multivariate analysis, advanced age (hazard ratio (HR): 1.68, 95% confidence interval (CI): 1.24-2.29), underweight (body mass index <18.5 kg/m2) (HR: 1.71, 95% CI: 1.25-2.32), previous stroke/SE/transient ischemic attack (HR: 1.70, 95% CI: 1.25-2.30), heart failure (HR: 1.59, 95% CI: 1.17-2.15), chronic kidney disease (HR: 1.53, 95% CI: 1.16-2.02), and anemia (HR: 2.41, 95% CI: 1.78-3.28) were independent predictors for death/stroke/SE. Cumulative numbers of these 6 risk predictors could stratify the incidence of death/stroke/SE in patients without OAC, as well as those with OAC in our registry.Advanced age, underweight, previous stroke/SE/transient ischemic attack, heart failure, chronic kidney disease, and anemia were independently associated with the risk of death/stroke/SE in non-anticoagulated Japanese AF patients.